2018
DOI: 10.1051/shsconf/20185604008
|View full text |Cite
|
Sign up to set email alerts
|

Blue Ocean Leadership and Emotional Intelligence in Government Link Companies (GLCs): Preparing for Industry 4.0

Abstract: This research is carried out to examine the influences of blue ocean leadership styles on emotional intelligence. A stratified random sampling technique is used to identify the sample for this study. Questionnaire is distributed to 120 middle to top level leaders from the selected government link companies (GLCs) which is listed in the Government Link Transformation Programme (GLTP). A partial least square structural model (PLS-SEM) approach is used to analyses the data for this study. The findings indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…According to the World Economic Forum (2019), leadership forms in 4.0 include accountability and responsibility, systems leadership, technological leadership, entrepreneurial leadership, adaptive leadership, and societal shaping. Hanafi, et al (2018) identified the following characteristics for leadership in the 4.0 era: visionary, courageous, passionate, strategic thinking/planning, focused, collaborative, innovative, eager to change, and communicative. The World Economic Forum (2021) recognised the 4.0 leadership paradigm as encompassing cross-hierarchical, agile, motivating, team-oriented, and digital leaders with accountability.…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Economic Forum (2019), leadership forms in 4.0 include accountability and responsibility, systems leadership, technological leadership, entrepreneurial leadership, adaptive leadership, and societal shaping. Hanafi, et al (2018) identified the following characteristics for leadership in the 4.0 era: visionary, courageous, passionate, strategic thinking/planning, focused, collaborative, innovative, eager to change, and communicative. The World Economic Forum (2021) recognised the 4.0 leadership paradigm as encompassing cross-hierarchical, agile, motivating, team-oriented, and digital leaders with accountability.…”
Section: Introductionmentioning
confidence: 99%